P-E14 An observational cohort of post-natal HIV transmission among women on HAART who breastfeed their infants in Nigeria: Findings from the INFANT study. (March 2017) - Osawe, Sophia; Datong, Pam; Cole, Chundung; Okolo, Felicia; Guyit, Ruth; Cameron, Bill; Rosenthal, Kenneth; Gray, Clive; Jaspan, Heather; Abimiku, Alash'le
Abstract : Introduction: Infants born to HIV-infected mothers, who do not acquire HIV in utero or perinatally, continue to be at risk of acquiring HIV through breastfeeding. The World Health Organization (WHO) guidelines recommend exclusive breastfeeding and HAART. Mothers with normal pregnancy and babies were enrolled. We analyse a cohort of mother-infant pairs in Nigeria and calculate HIV incident rate among breast-fed infants. The INFANT study is an observational cohort. Participants were recruited from Plateau State Specialist Hospital in Jos, Nigeria and followed for 2 years (April 2013 to March 2015). Mothers were included in the study their infants were ≥ 36 weeks of gestation and had a birth weight ≥2.4 kg. All infants infected in utero or at peripartal were excluded from the study. A survival analysis was used to calculate the incident rate of mother to child transmission. Discussion: A total of 384 HIV+ mother and infants were included in this analysis. The mothers' median age was 30 years. About 120 (31%), 153 (40%), 101 (26%) of the cohort had primary, secondary and higher education respectively. Almost all were married 370 (96%), 177 (46%) were self employed, and 352 (92%) reported living in a house but only 161 (42%) has refrigeration. Almost all mothers 383 (98%) exclusively breast at birth but the numbers dropped with each passing month. A reasonable number of mothers were not virologically suppressed, but only 2 infants were infected over the 2-year study period, giving this site an overall incidence of HIV-infection was 0.5/100 person-years (95% CI: 0.06 to 1.81). Conclusions: The study of post-natal mother to child transmission is highly relevant especially with the availability of HAART. This study has shown a low incidence rate of transmission via breastfeeding proving that breastfeeding is a safe and recommended practice for mothers living with HIV in our African setting.